Dynamic cache allocation routing strategy of Internet of things satellite node based on traffic prediction - Weidong WANG; Cheng WANG; Huiwen WANG; Pin XU (Tongxin xuebao, 2020)
Aiming at the routing problem of low earth orbit (LEO) Internet of things (IoT) satellite systems,a dynamic cache allocation routing strategy based on traffic prediction for IoT satellite nodes was proposed.Firstly,the space-time characteristics of traffic distribution in the LEO coverage area were analyzed,and an end-to-end traffic prediction model was proposed.Then,according to the traffic prediction result,a dynamic cache allocation routing strategy was proposed.The satellite node periodically monitored the traffic load of the inter-satellite link,dynamically allocated the cache resources of each inter-satellite link between the neighboring nodes.The cache allocation process was divided into two phases,initialization and system operation.At the same time,the traffic offload and packet forwarding strategy when the node was congested was proposed.By comparing the queuing delay and the forwarding delay,it was determined whether the data packet needs to be rerouted.The simulation results show that the proposed routing strategy effectively reduces the packet loss rate and average end-to-end delay,and improves the traffic distribution in the whole network.